2003
DOI: 10.1016/s0002-9440(10)63685-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Down-Regulation of Fli1, a Suppressor of Collagen Transcription, in Fibrotic Scleroderma Skin

Abstract: The molecular and cellular mechanisms that maintain proper collagen homeostasis in healthy human skin and are responsible for the dysregulated collagen synthesis in scleroderma remain primarily unknown. This study demonstrates that Fli1 is a physiological negative regulator of collagen gene expression in dermal fibroblasts in vitro and in human skin in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 158 publications
(159 citation statements)
references
References 45 publications
11
147
1
Order By: Relevance
“…For immunostainings, we used primary antibodies against total Smad1 (Abcam, Cambridge, MA) and phospho-Smad1 (17). Incubations with the primary antibodies diluted in horse serum in PBS to the indicated concentrations were performed overnight in a humidified chamber at 4°C as previously described (18). After 3 rinses in PBS, binding sites of the primary antibodies were detected with biotinylated IgG, and the sites of peroxidase activity were visualized by using diaminobenzidine.…”
Section: Methodsmentioning
confidence: 99%
“…For immunostainings, we used primary antibodies against total Smad1 (Abcam, Cambridge, MA) and phospho-Smad1 (17). Incubations with the primary antibodies diluted in horse serum in PBS to the indicated concentrations were performed overnight in a humidified chamber at 4°C as previously described (18). After 3 rinses in PBS, binding sites of the primary antibodies were detected with biotinylated IgG, and the sites of peroxidase activity were visualized by using diaminobenzidine.…”
Section: Methodsmentioning
confidence: 99%
“…Reduction of Fli1 gene expression by TGF-␤ suggested that the presence of Fli1 might interfere with TGF-␤/Smad signaling. To test this possibility, we used previously generated adenoviral vector carrying Fli1 (AdFli1) (29). Cells were transduced with 10 MOI of AdFli1, which resulted in 8 -10-fold induction of the Fli1 mRNA level above the endogenous levels.…”
Section: Opposite Effects Of Ets1 and Fli1 On The Expression Levels Omentioning
confidence: 99%
“…Fli1 and Ets1 have been previously associated with regulation of ECM genes, including collagen type I and tenascin-C (14,15). Importantly, reduction of Fli1 expression correlated with elevated collagen synthesis in patients with scleroderma, a systemic fibrotic disease, suggesting that absence of Fli1 may directly contribute to the process of fibrosis (29). On the other hand, elevated expression of Ets1 is often present in stromal fibroblasts and endothelial cells in various tumors (5).…”
mentioning
confidence: 99%
“…1). Furthermore, different Ets factors may have reciprocal functions: Ets1 and Fli1 differentially regulate the collagen α2(I) promoter [Czuwara-Ladykowska et al, 2001;Kubo et al, 2003]. Thus, the precise balance or "regulated imbalance" between cancer/metastasispromoting and-inhibiting Ets factor activities, which differentially regulate specific target genes, contributes to tissue homeostasis or tumor progression, respectively.…”
Section: Ets Target Genesmentioning
confidence: 99%